Aspek Laboratorium Gagal Ginjal Kronik - Febtarini Rahmawati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
Chronic renal disease is a disorder of renal function or structure that lasts for more than three months, accompanied by a decrease in glomerular filtration rate. Decreasing of renal function monitoring is performed by measuring glomerular filtration rate, determining blood urea, creatinine, creatinine clearance, electrolytes, uric acid, blood gas analysis and tubular function. The Recent method for measuring glomerular filtration rate using inulin clearance, however, is not efficient. Further measurements of creatinine glomerular filtration rate were developed. Measurements of urea, creatinine and uric acid are currently using enzymatic methods of spectrophotometry, while electrolyte examination by selective ion electrode method. Blood gas analysis determined pH, PCO2, PO2, HCO3-, CO2 total, base excess and SO2. Examination of urine protein and urine sediments helps establish a diagnosis of chronic kidney disease